2, 4-Dichlorophenol removal by purified horseradish peroxidase enzyme and crude extract from horseradish immobilized to nano spray dried ethyl cellulose particles. Issue 11 (November 2015) - Dahili, Laura Amina; Kelemen-Horváth, Ilona; Feczkó, Tivadar
Graphical abstract: Highlights: Fine ethyl cellulose particles were prepared by nano spray drying method. Purified and extracted horseradish peroxidase was immobilized on fine ethyl cellulose carrier. Immobilization of horseradish peroxidase improved its pH tolerance and storing stability. The immobilized enzyme removed efficiently 2, 4-dichlorophenol (>90%). Concentration of 2, 4-dichlorophenol and H2 O2 influenced mostly the substrate conversion. Abstract: Horseradish peroxidase (HRP) is a promising catalyst in the enzymatic process of phenolic compounds removal from wastewaters. Enzyme immobilization provides important benefits in a biotechnological process. Fine particles with a high surface-to-volume ratio composed of ethyl cellulose (EC) polymer were generated by Nano Spray Dryer B-90 as supports for HRP. Carrier particles were prepared by spray caps with hole size of 7 μm, 5.5 μm and 4 μm. Purified HRP and crude extract from horseradish were covalently bound to the carrier using a carbodiimide cross-linker. The attached HRP content, the effect of pH on the activity and the storage stability were investigated. 2, 4-dichlorophenol, an extremely persistent chlorinated phenol was removed by the immobilized enzyme, and the effect of main process parameters such as H2 O2 and 2, 4-dichlorophenol substrate concentrations were studied. After immobilization both the purified HRP and the horseradish extract performed better in the pH range of 4–10 and could preserve the activity substantially longer than the free enzyme. The immobilized enzyme was found to be outstandingly efficient (in optimal case close to 100%) in the elimination of 2, 4-dichlorophenol, which was also the consequence of the high adsorbing capacity of the fine particles. The reuse study proved the operational stability of HRP attached to EC even after 10 consecutive cycles.